RNA Binding Protein Motif 3 Inhibits Oxygen-Glucose Deprivation/Reoxygenation-Induced Apoptosis Through Promoting Stress Granules Formation in PC12 Cells and Rat Primary Cortical Neurons - Si, Wenwen; Li, Zhen; Huang, Zifeng; Ye, Shanyu; Li, Xinrong; Li, Yi; Kuang, Weihong; Chen, Dongfeng; Zhu, Meiling (Frontiers in Cellular Neuroscience, 2020)
As a sensitive cold-shock protein, RNA binding protein motif 3 (RBM3) exhibits a neuroprotective function in the condition of brain injury. However, how RBM3 is involved in acute ischemic stroke by affecting stress granules (SGs) remains unclear. Here, we established an oxygen-glucose deprivation/reperfusion (OGD/R) model in rat primary cortical neurons and PC12 cells to explore the potential mechanism between RBM3 and SG formation in acute ischemic/reperfusion (I/R) condition. The immunofluorescence results showed that the SG formation significantly decreased in rat primary cortical neurons and PC12 cells during the reperfusion period after 6 h of OGD stimulation. The western blot results, flow cytometry analysis, and cell viability assessment showed that the RBM3 expression and ratio of cell viability significantly decreased, while the rate of apoptosis increased in PC12 cells during the reperfusion period after 6 h of OGD stimulation. Co-immunoprecipitation (Co-IP) and immunofluorescence indicated that RBM3 and GTPase-activating protein-binding protein 1 (G3BP1) colocalized cytoplasm of PC12 cells after 6 h of OGD stimulation when the SGs formation reached the highest level. Besides, overexpression and knockdown of the RBM3 were achieved via plasmid transfection and CRISPR-Cas9 technology, respectively. The results of overexpression and knockdown of RBM3 gene illustrated the pivotal role of RBM3 in affecting SG formation and apoptosis level in OGD-treated PC12 cells. In conclusion, RBM3 could combine with G3BP1 resulted in increasing stress granules generation in rat primary cortical neurons and PC12 cells after 6 h of oxygen-glucose deprivation (OGD) injury, which ultimately reduced the apoptosis in OGD-induced cells. Our study may enable a new promising target for alleviating ischemia-reperfusion injury in cells.